2016
DOI: 10.1016/j.jtho.2016.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer in the Very Young: Treatment and Survival in the National Cancer Data Base

Abstract: Overall and relative survival in younger patients with NSCLC is better than in older patients, with greater benefit seen in earlier stages. Despite having fewer comorbidities and undergoing more aggressive treatment, younger patients with advanced-stage NSCLC have only marginally better overall and relative survival than older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 24 publications
12
74
0
Order By: Relevance
“…Cancers such as breast cancer, colon cancer, and acute lymphoblastic leukemia are understood to present a distinct disease biology in patients diagnosed at a young age . In contrast, NSCLC in the young is a poorly studied clinical entity . It has been reported that 70 years of age was the median age for diagnosis of NSCLC and patients diagnosed younger than 50 years accounted for less than 5% of patients .…”
Section: Introductionmentioning
confidence: 99%
“…Cancers such as breast cancer, colon cancer, and acute lymphoblastic leukemia are understood to present a distinct disease biology in patients diagnosed at a young age . In contrast, NSCLC in the young is a poorly studied clinical entity . It has been reported that 70 years of age was the median age for diagnosis of NSCLC and patients diagnosed younger than 50 years accounted for less than 5% of patients .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that age has been recognized as a significant prognostic factor in some tumors. In non-small cell lung cancer, younger patients take advantage in overall and relative survival, particularly at earlier stage [12]. By contrast women with breast cancer aged 35 years or younger are recommended to adopt additional risk-reduction strategies after radical treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, younger patients (less than 50 years of age) with NSCLC have been reported to have better survival outcomes when compared to older patients [3,4]. In contrast, very little data have been reported with regard to young patients with SCLC.…”
Section: Introductionmentioning
confidence: 99%